2019
DOI: 10.1111/vsu.13221
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative morbidity and mortality in dogs with invasive adrenal neoplasms treated by adrenalectomy and cavotomy

Abstract: Objective To report the morbidity and mortality associated with adrenalectomy with cavotomy for resection of invasive adrenal neoplasms in dogs and evaluate risk factors for perioperative outcomes. Study design Retrospective study. Animals Forty‐five client‐owned dogs. Methods Dogs that underwent open adrenalectomy with cavotomy for resection of adrenal masses with tumor thrombus extending into the vena cava were included. Clinicopathologic data were harvested from medical records. Selected clinical, imaging, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(62 citation statements)
references
References 16 publications
(64 reference statements)
2
60
0
Order By: Relevance
“…1,[3][4][5]11,12 A recent study revealed that adrenalectomy with cavotomy for resection of tumour thrombus within the vena cava can be challenging and short-term mortality can be high. 17 The short-term mortality was influenced by pre-and postdiaphragmatic thrombus extension. Only 40% of dogs survived with post-diaphragmatic thrombus extension compared with 73 to 81% survival in dogs with a thrombus terminating pre-diaphragmatically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,[3][4][5]11,12 A recent study revealed that adrenalectomy with cavotomy for resection of tumour thrombus within the vena cava can be challenging and short-term mortality can be high. 17 The short-term mortality was influenced by pre-and postdiaphragmatic thrombus extension. Only 40% of dogs survived with post-diaphragmatic thrombus extension compared with 73 to 81% survival in dogs with a thrombus terminating pre-diaphragmatically.…”
Section: Discussionmentioning
confidence: 99%
“…This controversy is likely because of the high perioperative mortality rates previously reported in the veterinary literature 1,3,4,5,11,12 . A recent study revealed that adrenalectomy with cavotomy for resection of tumour thrombus within the vena cava can be challenging and short‐term mortality can be high 17 . The short‐term mortality was influenced by pre‐ and post‐diaphragmatic thrombus extension.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, CEUS is performed in real time and allow to monitor continuously the contrast distribution, whereas in CT the selection of the vascular phase, i.e., the timing of the acquisition compared to the intravenous injection of the contrast agent, can influence the detection of thrombosis [15]. In small animals CT, the limited spatial resolution and the possible presence of streamlining artifact could reduce the possibility to correctly diagnose thrombosis [23], and CT may also be unable to detect endothelial invasion or evaluate the risk of fragmentations, both important features for a correct surgical planning [10].…”
Section: Discussionmentioning
confidence: 99%
“…Fast and less invasive surgical techniques have been recently described in dogs with caval invasion, with good results [8,9], despite the presence of a post-hepatic thrombus or long caval occlusion time [9]. According to another recent study, dogs with post-diaphragmatic tumor thrombi still showed a worse prognosis [10]. Therefore, detection and characterization of tumor thrombi is of great importance in patients with primary tumors for both surgical planning and prognosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation